2020
DOI: 10.1590/0001-3765202020191364
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome diversity in species of the genus Arachis, revealed by FISH and CMA/DAPI banding, and inferences about their karyotype differentiation

Abstract: The species of the genus Arachis (Leguminosae) are ordered into nine sections. The assignment of genome types in this genus has been based on cross-compatibility analysis and molecular cytogenetic studies. The latter has also allowed karyotypically establishing well-defined genomes and reassigning the genome of several species. However, most of these studies have been focused mainly on the sections Arachis and Rhizomatosae. To increase the knowledge about the chromosome diversity of the whole genus, here we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Regular bivalent formation has also been reported for other autopolyploids, as Arabidopsis arenosa (Carvalho et al, 2010), and autopolyploidy may be not as rare as supposed earlier (Soltis et al, 2007). The assumption of an autopolyploid origin for Z. brachiandra could also explain the many duplicated patterns of chromosome banding and rDNA site distribution observed here, some of them blurred by the intense heteromorphism characteristic of heterochromatic bands and rDNA sites (Chalup et al, 2015;Silvestri et al, 2020;Ribeiro et al, 2021). Five other species of Zephyranthes analysed by Felix et al (2011b) revealed a much smaller and variable number of CMA + bands and no DAPI + bands, suggesting that a cytomolecular investigation of other Zephyranthes species would be very helpful to understand the cytotaxonomy and chromosomal evolution of this group.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Regular bivalent formation has also been reported for other autopolyploids, as Arabidopsis arenosa (Carvalho et al, 2010), and autopolyploidy may be not as rare as supposed earlier (Soltis et al, 2007). The assumption of an autopolyploid origin for Z. brachiandra could also explain the many duplicated patterns of chromosome banding and rDNA site distribution observed here, some of them blurred by the intense heteromorphism characteristic of heterochromatic bands and rDNA sites (Chalup et al, 2015;Silvestri et al, 2020;Ribeiro et al, 2021). Five other species of Zephyranthes analysed by Felix et al (2011b) revealed a much smaller and variable number of CMA + bands and no DAPI + bands, suggesting that a cytomolecular investigation of other Zephyranthes species would be very helpful to understand the cytotaxonomy and chromosomal evolution of this group.…”
Section: Discussionmentioning
confidence: 70%
“…Within certain limits, the amount of heterochromatin is not critical to genome function but in a few species it is enormously expanded, forming large heterochromatic blocks, as in Trithrinax campestris and Capsicum species (Gaiero et al, 2012;Grabiele et al, 2018), or numerous small bands, as in Cuscuta monogyna (Ibiapino et al, 2020). The tandemly repeated nature of rDNA and telomeric DNA sites allows a considerable variation in number and size of these sites, contributing to a better karyotype characterization of species or populations (Pedrosa-Harand et al, 2006;Robledo & Seijo, 2010;Rosato et al, 2017Rosato et al, , 2018Silvestri et al, 2020). Currently, chromosome staining with the fluorochromes chromomycin A 3 (CMA) and 4',6-diamidino-2phenylindole (DAPI) is the most used method to differentiate GC-rich and AT-rich heterochromatic bands, respectively (Guerra, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single GISH experiments on the A. pusilla chromosomes (Am genome) using A. glabrata gDNA probes revealed only six clear hybridization signals (Figures 1a and 1b) located at the 18-26S rDNA loci described for the species (Silvestri et al 2020). Similarly, the hybridization onto the metaphases of A. burkartii (R genome) revealed two strong signals corresponding to the larger 18-26S rDNA loci of the satellite chromosomes.…”
Section: Resultsmentioning
confidence: 93%
“…However, in case of L. culinaris and related species, AT heterochromatic regions were mapped by repetitive sequence probe FISH (Galasso et al 2001;Galasso 2003). Also in Papilionoideae, AT rich heterochromatin at centromere and pericentromeric regions are reported in Vigna (Bortoleti et al 2012;She et al 2020), Lablab and Arachis (Silvestri et al 2020). Nonetheless, occurrence of centromeric CMA + or DAPI + bands along with nucleolar CMA + /DAPI + or CMA 0 bands certainly advocate atypical heterochromatin composition in Lens.…”
Section: Discussionmentioning
confidence: 99%